Creating Public Participation Processes for The Development of ’Kaem Ling’ (Monkey Cheek) Water Retention Areas in Koh Po Sub-District, Nong Chik District, Pattani Province - กูนิง นูรียะห์; ยูโซ๊ะ มูฮำหมัดฟาอิส; ดานิ ซีตีฟาตีเมาะ; บินอิสริส วันฮารงค์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to (1) examine the process of public participation in the development of the Kaem Ling (Monkey Cheek) Project in Ko Po Subdistrict, Nong Chik District, Pattani Province; and (2) propose guidelines to promote and enhance effective and sustainable public participation in the development of the project area. The study employed a qualitative research methodology. Data were collected from 29 key informants, including community leaders, community representatives, government officials, and local stakeholders, through in-depth interviews, focus group discussions, and participant observation. The data were analyzed using content analysis and descriptive interpretation. The findings indicated that 1) public participation occurred in the forms of receiving information, participating in activities, and expressing opinions in community forums. However, participation in policy decision-making processes remained limited. Key factors influencing participation included trust in government agencies, the role of community leaders, open communication, and awareness of the project’s benefits. And 2) Appropriate development guidelines should promote two-way communication, create spaces for knowledge exchange, and strengthen the capacity of local leaders to enable people to participate in all stages of the development process, leading to community empowerment and the long-term sustainability of the project